2020
DOI: 10.17221/27/2019-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Minimal morphoagronomic descriptors for Cuban pineapple germplasm characterisation

Abstract: A set of minimum descriptors allow for the rapid characterisation of germplasm facilitating the conservation and use of plant material. The objective of this work was to establish a list of minimum descriptors to facilitate the morphological characterisation of the ex situ pineapple collection in Cuba. Therefore, 48 pineapple accessions were characterised according to the morphoagronomic descriptors established by the International Board for Plant Genetic Resources (IBPGR). The data were processed by Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…Out of 49 characters observed, there was 12 selected character that contributed significantly to the variation in pineapple plants on peatland. The number of characters found in this study was less than that reported by Rodriguez-Alfonso et al (2020), with 14 characters were distinguishing pineapple plants in Cuba. Fruit shape, eye profile, eye surface, flesh color, fruit diameter, crown weight are characters that have a significant contribution to diversity (Rodriguez-Alfonso et al 2020).…”
Section: Principal Component Analysis (Pca) Of Quantitative Charactercontrasting
confidence: 87%
See 2 more Smart Citations
“…Out of 49 characters observed, there was 12 selected character that contributed significantly to the variation in pineapple plants on peatland. The number of characters found in this study was less than that reported by Rodriguez-Alfonso et al (2020), with 14 characters were distinguishing pineapple plants in Cuba. Fruit shape, eye profile, eye surface, flesh color, fruit diameter, crown weight are characters that have a significant contribution to diversity (Rodriguez-Alfonso et al 2020).…”
Section: Principal Component Analysis (Pca) Of Quantitative Charactercontrasting
confidence: 87%
“…Although this technique has several weaknesses, such as it depends on the season and growth phase of the plant, the morphological identification provides an overview that can directly be distinguished from differences in characters and advantages of a genotype. The use of morphological characters in pineapple identification has been reported by Hadiati et al (2003), Machado et al (2011), Burhooa & Ranghoo-sanmukhiya (2012), Hernita et al (2019), andRodriguez-alfonso et al (2020) using some of the available characters. The use of many characters in identification often results in excessive information (Daher et al 1997) because of the many correlated characters or low genetic diversity.…”
Section: Geneticmentioning
confidence: 98%
See 1 more Smart Citation